ASFIKSIA FAKTOR DOMINAN PENYEBAB KEMATIAN NEONATAL - Siti Masitoh Masitoh; Theresia EVK EVK; Karningsih Karningsih Karningsih (Poltekkes Kemenkes Jakarta III, 2014)
Neonatal death is number of infant deaths up to 4 weeks of age per 1000 live births in the year. One attempt to reduce neonatal mortality rate is a know risk factor of which came from the maternal, neonatal, pregnancy and childbirth factors research objectives to determine the correlation between mothers and neonates with neonatal mortality. Casecontrol study. Sample size is 80 with random sampling method.. The result of the 80 responden found the majority of woman aged 20 - 35 years 65 (81,3 %), not working 48 (60 %), parity is 1 - 3 for 59 (73,8 %) and complications of childbirth 47 (58,8 %). Based on factors largely neonatal asphyxia 44 (55 %), not LBW 50 (62,9 %), not gemelli 72 (90 %) and 37- 40 weeks of gestation 53 (66,3 %). Test result Chi-Square of 8 obbtained significant six variables are age, parity, employment, asphyxia, LBW and gestation. Test result Logistic Regression risk age < 20 and >35 years of neonatal death was 6.5 times greater than the age 20 - 35 years. Parity >3 had a7.9 times greater than parity 1 - 3. Asphyxia has a 21.3 times greater risk compared to neonatal not asphyxis. The greatest influence on neonatal death was asphyxia after controlling the variables of age and parity.